2006
DOI: 10.1110/ps.062136006
|View full text |Cite
|
Sign up to set email alerts
|

Native state energetics of the Src SH2 domain: Evidence for a partially structured state in the denatured ensemble

Abstract: We have defined the free-energy profile of the Src SH2 domain using a variety of biophysical techniques. Equilibrium and kinetic experiments monitored by tryptophan fluorescence show that Src SH2 is quite stable and folds rapidly by a two-state mechanism, without populating any intermediates. Native state hydrogen-deuterium exchange confirms this two-state behavior; we detect no cooperative partially unfolded forms in equilibrium with the native conformation under any conditions. Interestingly, the apparent st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
31
2

Year Published

2006
2006
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(36 citation statements)
references
References 46 publications
1
31
2
Order By: Relevance
“…Upon local or global unfolding (deprotection) the cleavage site adopts the 'open' state and is exposed to hydrolytic attack. This two-state model has had wide acceptance for a variety of protein systems (50,(60)(61)(62), and the observed kinetic trends for Cp149 validate the two-state model for this application (or details, see Discussion).…”
Section: Kinetic Modelmentioning
confidence: 69%
“…Upon local or global unfolding (deprotection) the cleavage site adopts the 'open' state and is exposed to hydrolytic attack. This two-state model has had wide acceptance for a variety of protein systems (50,(60)(61)(62), and the observed kinetic trends for Cp149 validate the two-state model for this application (or details, see Discussion).…”
Section: Kinetic Modelmentioning
confidence: 69%
“…The proteins used in this study were drawn from those reported in studies by Myers et al and Hong et al, along with some we added (7,(29)(30)(31)(32)(33)(34)(35). The m values depend on salt concentration and pH, so only those proteins are included that are monomeric, denature reversibly in the presence of urea at neutral pH and moderate salt, exhibit two-state behavior, and contain no cofactor or metal ion.…”
Section: Discussionmentioning
confidence: 99%
“…We were thus able to calculate the free energies of the denaturant-independent local fluctuations (ΔG LF ) and of the denaturant-dependent sub-global unfolding events (ΔG UNF ), and the value of m ex , the denaturant-dependence of ΔG UNF . 40 ΔG ex versus[Gu-HCl] plots for representative residues are shown in Fig. 5.…”
Section: Cooperative Folding Unitsmentioning
confidence: 99%
“…6a and b 40 By contrast, for a protein with multiple unfolding units, residues from independent unfolding units would be characterized by their different ΔG UNF and m ex -values. The group of residues with the highest energy represents the global unfolding of the protein and the groups with lower energy reveal partially unfolded species.…”
Section: Cooperative Folding Unitsmentioning
confidence: 99%